What is -8c+8c-12 when you are simplifying

Answers

Answer 1

Answer:

Multiply c and 8

Multiply c and 1

The c just gets copied along.

The answer is c

c

8*c evaluates to 8c

Because of the minus sign

8c becomes - 8c

The answer is -8c

Multiply c and 8

Multiply c and 1

The c just gets copied along.

The answer is c

c

8*c evaluates to 8c

-8*c+8*c evaluates to 0c

-8*c+8*c-12 evaluates to -12

The final answer is

-12

Step-by-step explanation:

Please mark brainliest and have a great day!


Related Questions

DBE is obtained by enlarging ABC. If the area of ABC is 3 square units, what is the area of DBE?

Answers

Answer:

The area of DBE = 27 square units

Step-by-step explanation:

Area of ABC = 3 square units

In the figure, we can see that ABC was enlarged so that BDE is formed where side BD = 6 and AB was = 2

Hence ABC was enlarged 3 times its size.

We know by formula that:

Area of ABC = 1/2(base x perpendicular)

3 = 1/2(2 x p)

=> p = 3

As ABC was enlarged 3 times its size, the perpendicular of BDE must be 3*p

= 3*3 = 9

AREA OF DBE = 1/2(base*perp)

= 1/2(6*9)

= 27 square units

Answer:

The area of DBE = 27 square units

Step-by-step explanation:

Area of ABC = 3 square units

In the figure, we can see that ABC was enlarged so that BDE is formed where side BD = 6 and AB was = 2

Hence ABC was enlarged 3 times its size.

We know by formula that:

Area of ABC = 1/2(base x perpendicular)

3 = 1/2(2 x p)

=> p = 3

As ABC was enlarged 3 times its size, the perpendicular of BDE must be 3*p

= 3*3 = 9

AREA OF DBE = 1/2(base*perp)

= 1/2(6*9)

= 27 square units

Step-by-step explanation:

4log9(3)=log9? I need to make the equation true any help would be much appreciated

Answers

[tex]\bf \textit{Logarithm of exponentials} \\\\ \log_a\left( x^b \right)\implies b\cdot \log_a(x) \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ 4\log_9(3)=\log_9(x)\implies \log_9(3^4)=\log_9(x)\implies 3^4=x\implies 81=x[/tex]

The value of x will be equal to 81.

What is an expression?

Expression in maths is defined as the collection of the numbers variables and functions by using signs like addition, subtraction, multiplication and division

4log₉(3)   =  log₉x

By using the logarithmic property:-

Log[tex]_a[/tex]( x[tex].^b[/tex])  =  b Log[tex]_a[/tex](x)

4log₉(3)   =  log₉x

log₉ ( 3 )⁴  =  log₉ ( x )

3⁴   =  x

x   =  81

Therefore the value of x will be equal to 81.

To know more about Expression follow

https://brainly.com/question/723406

#SPJ2

Find the value of x for the expression 4(4^x-2^x)+1=0

Answers

Answer:

x = -1

Step-by-step explanation:

[tex]4(4^x-2^x)+1=0\\\\4\bigg((2^2)^x-2^x\bigg)+1=0\qquad\text{use}\ (a^n)^m=a^{nm}\\\\4(2^{2x}-2^x)+1=0\\\\4\bigg((2^x)^2-2^x\bigg)+1=0\qquad\text{substitute}\ 2^x=t>0\\\\4(t^2-t)+1=0\qquad\text{use the distributive property}\\\\4t^2-4t+1=0\\\\4t^2-2t-2t+1=0\\\\2t(2t-1)-1(2t-1)=0\\\\(2t-1)(2t-1)=0\\\\(2t-1)^2=0\iff2t-1=0\qquad\text{add 1 to both sides}\\\\2t=1\qquad\text{divide both sides by 2}\\\\t=\dfrac{1}{2}[/tex]

[tex]\text{We're going back to substitution}\\\\t=\dfrac{1}{2}\Rightarrow2^x=\dfrac{1}{2}\qquad\text{use}\ a^{-1}=\dfrac{1}{a}\\\\2^x=2^{-1}\iff x=-1[/tex]

solving quadratic equations using squares
x^2 +6x-7=0​

Answers

Answer:

x = 1 or x = -7

Step-by-step explanation:

Step-by-step explanation:

Do you mean by completing the square?

x² + 6x - 7 = 0

x² + 6x = 7

Take half of 6, square it, and add to both sides.  (6/2)² = 9.

x² + 6x + 9 = 7 + 9

(x + 3)² = 16

x + 3 = ±4

x = -3 ± 4

x = -7, 1

So the roots are x=-7 and x=1.

If (x) = 3х - 2 and g(x) = 2х+ 1, find (f- g)(x).
ОА. х- з
Ов. 3-х
Ос. 5x - 1
OD. 5x - з

Answers

Answer:

A

Step-by-step explanation:

f(x) - g(x) = 3x-2 - (2x + 1)      Remove the brackets

f(x) - g(x) = 3x - 2 - 2x -1       Combine terms.

f(x) - g(x) = x - 3

The answer is A

What is the quotient of 33.32 ÷ 9.8 =

Answers

Answer: 3.4

33.32/9.8= 3.4

Answer:3.4

Step-by-step explanation:

AD diameter of Circle P, if m 1 = 40 then m AB = 20, 40, 80 PLEASE HELP​

Answers

Answer:

40 it is a trick question

Step-by-step explanation:

Answer:

The correct option is:   40

Step-by-step explanation:

Measure of an arc is actually the measure of the central angle corresponding with that same arc.

Here, the corresponding central angle for arc [tex]\widehat{AB}[/tex] is [tex]\angle1[/tex].

Given that,  [tex]m\angle 1= 40[/tex]°

So.....

[tex]m\widehat{AB}=m\angle 1\\ \\ m\widehat{AB}=40\°[/tex]

Find the area and perimeter of the following figure​, please help a.s.a.p

Answers

Perimeter:
P=2(5+2)+2(3)+2+(3-1)
=24m
Area:
A=5(3)+2(1)+2(1)
=15+2+2
=19m^2

I'm just done with math... as long as you explain it I'll mark your brainiest.

Answers

Answer:

The correct answer is the third option

Step-by-step explanation:

Have different slope but have the same y-intercept, so they have no solution.

y = 1/2x - 3

To graph this, the slope 1/2 which means go up once and to the right twice and b = -3, which means the y-intercept.

second equation:

y =  -1/2x -3

To graph this, the slope -1/2 which means go down once and to the right twice and b = -3, which means the y-intercept.

Please mark as brainliest

What is the distance from A to A’?

Answers

Answer: I think problem 2

Step-by-step explanation: hope this helps

Which expression is equivalent to the expression below?

Answers

Answer:

[tex]\frac{1}{(m-4)(m-3)}[/tex]

Step-by-step explanation:

The question requires you to simplify using quadratic identities

Re-write the numerator.

[tex]\frac{m+3}{m^2-16} \\\\\\\\=\frac{m+3}{(m+4)+(m-3) }[/tex]

Re-write the denominator as;

[tex]\frac{(m+3) +(m-3)}{m+4}[/tex]

Re-arrange expression

[tex]\frac{m+3}{(m+4)+(m-4)} * \frac{m+4}{(m+3)+(m-3)}[/tex]

cancel the terms that are alike to remain with

[tex]\frac{1}{(m-4)(m-3)}[/tex]

Answer:

The expression which equivalent is 1/[(m - 4)(m - 3)] ⇒ 2nd answer

Step-by-step explanation:

* Lets revise how to divide two fractions

- To divide a/b and c/d change the division operation to multiplication

  operation and reciprocal the fraction after the division sign

# a/b ÷ c/d = a/b × d/c

* Lets solve the problem

∵ (m + 3)/(m² - 16) ÷ (m² - 9)/(m + 4)

- Use the factorization to simplify the fractions

∵ m² - 16 is a different of two squares

- The factorization of the different of two squares a² - b² is

∵ a² = a × a , -b² = b × -b

∴ a² - b² = (a + b)(a - b)

- Use this way with m² - 16

∵ m² = m × m

∵ -16 = 4 × -4

∴ m² - 16 = (m + 4)(m - 4)

- Similar factorize m² - 9

∵ m² = m × m

∵ -9 = 3 × -3

∴ m² - 9 = (m + 3)(m - 3)

- Now lets write the fraction and simplify it

∵ (m + 3)/(m² - 16) ÷ (m² - 9)/(m + 4)

∴ (m + 3)/[(m + 4)(m - 4)] ÷ [(m + 3)(m - 3)]/(m + 4)

- Change the division operation to multiplication operation and

  reciprocal the fraction after the division sign

∴ (m + 3)/[(m + 4)(m - 4)] × (m + 4)/[(m + 3)(m - 3)]

- We can cancel (m + 4) in the denominator of the first fraction with

 (m + 4) in the numerator of the second fraction and cancel (m + 3)

 in the numerator of the first fraction with (m + 3) in the denominator

 of the second fraction

∴ 1/(m - 4) × 1/(m - 3) ⇒ multiply the two fractions

∴ 1/[(m - 4)(m - 3)]

* The expression which equivalent is 1/[(m - 4)(m - 3)]

There are 30 students in a class. The teacher will choose 2 students at random to represent the class at an assembly. How many groups of 2 students can be chosen? A. 870 B. 435 C. 60 D. 15

Answers

Answer:

The answer to this question is D- 15.

Step-by-step explanation:

This is how to solve it

30 students and 2 at random this are the key words

you do 30/2

your answer is equal to 15

Answer: B. 435

Step-by-step explanation: This is a combination problem. The teacher is going to choose two students at random, but the order in which the two students are chosen doesn't matter. (meaning, student A being chosen 1st and student B being chosen 2nd is the same result as Student B being chosen 1st and student A being chosen 2nd) Since this is a combination's problem, we use the combination function nCr.

The nCr function is written as [tex]\frac{n!}{r!(n-r)!}[/tex], where n represents the total number of things to choose from while r represents the number of objects  that will be taken from the set. In this case, n=30 since there are 30 total students to choose from while r=2 since the teacher is picking two students from the group of 30.  The exclamation marks next to the variables represent a factorial.

A factorial is the product of all positive integers less than or equal to the integer next to the factorial. For example, 6! indicates 6 factorial, which is equal to 6 x 5 x 4 x 3 x 2 x 1 = 720. Therefore, 30! equals 30 x 29 x 28 x 27 x 26......... and so on until its been multiplied by every positive integer less than 30.

Using the nCr function, we plug the values in to get [tex]\frac{30!}{2!(30-2)!}[/tex]. After doing some simplification and factoring, we get the equation [tex]\frac{30 * 29}{2}[/tex], which yields 435 possible combinations. This can be done because 30 factorial and 28 factorial share 28 factors due to the nature of factorials, simplifying 30 factorial to simply 30 multiplied by 29. The equation yields 435 possible combinations, thus meaning that there are 435 possible ways to choose 2 students from 30 students.

During one day, the value of a stock lost
then gained 7 points (+7) in the after
of the stock's value for that day?
of a stock lost 4 points (4) in the morning and
in the afternoon. What was the overall loss or gain

Answers

11 is your answer and if it is wrong tell me the question in a more easier way

Find 3 ordered pair solutions by completing the table

x-y=4

Table:
Blank, 0
2, blank
Blank, -1

What are the blank ones?

Answers

Answer:

4 is the first blank

-2 is the second blank

3 is the third blank

Step-by-step explanation:

Table:

x   |  y

__    0         So this means we replace y with 0 in x-0=4 which means x=4

4      0    

4 is the first blank

Table:

x |  y

2   ___     So this means we replace x with 2 in 2-y=4 which means y=-2

2   -2

-2 is the second blank

Table:

x  | y

__  -1    So this means we replace y with -1 in x-(-1)=4 which means x=3

3    -1

3 is the third blank

Could anyone help me with this

Answers

Answer:

A

Step-by-step explanation:

U can already eliminate C and D since the z needs to be with 2. A and B almost look the same but in the radicals the second number goes on top resulting in 5/6 which leads to A.

An air conditioning system can circulate 390 cubic feet of air per minute. How many cubic yards of air can it circulate per​ minute?

Answers

The air conditioning system can circulate approximately 14.44 cubic yards of air per minute.

To convert cubic feet to cubic yards, we need to know that there are 27 cubic feet in one cubic yard. Using this conversion factor, we can find the number of cubic yards of air that the air conditioning system can circulate per minute.

1. Start with the given value of 390 cubic feet per minute.

2. Divide this value by the conversion factor of 27 cubic feet per cubic yard:

390 cubic feet ÷ 27 cubic feet per cubic yard = 14.44 cubic yards

3. Rounding to the nearest hundredth, the air conditioning system can circulate approximately 14.44 cubic yards of air per minute.

In summary, the air conditioning system can circulate approximately 14.44 cubic yards of air per minute.

Find the area of a square with a diagonal of 8 cm.

Answers

Answer:

To find the area of a square with only the diagonal known,

Square the diagonal and divide by 2:

8^2 = 64

64/2 = 32

The area is 32 cm^2

Answer:

32

Step-by-step explanation:

I’m correct

What is 4(x2 – 3x) + 12x2 + x simplified?
F 4x2–3x H 16x2–11x G13x2–2x I16x2–12x

Answers

Answer:

H 16x2–11x

Step-by-step explanation:

4(x2 – 3x) + 12x2 + x

4x^2-12x + 12x^2+x=

16x^2-11x

H 16x2–11x

The simplified value of  4(x² – 3x) + 12x² + x will be 16x² – 11x, i.e. option H.

What is system of equations?

System of equations is a finite set of equations for which common solutions are sought.

We have,

4(x² – 3x) + 12x² + x

Now,

Simplify the given equation by removing brackets,

i.e.

4x² – 12x + 12x² + x

Now,

Add or subtract the like terms,

i.e.

16x² – 11x

So, the simplified value of the given equation is 16x² – 11x .

Hence, we can say that the simplified value of  4(x² – 3x) + 12x² + x will be 16x² – 11x, i.e. option H.

To know more about system of equations click here

https://brainly.com/question/22460711

#SPJ2

Which expression gives the distance between the points (4,6) and (7,-3)

Answers

Answer:

D = 9.4868

Step-by-step explanation:

The expression is the following

D = √((x2-x1)^2+(y2-y1)^2)

Where

(x1,y1) = (4,6)

(x2,y2) = (7,-3)

D = √((7-4)^2+(-3-6)^2)

D = √((3)^2+(-9)^2)

D = √(9+81)

D = √(90)

D = 9.4868

Answer:

[tex]d = \sqrt{(7-4)^{2}+(-3-6)^{2}}[/tex]

Step-by-step explanation:

The expression used for calculating distance between two points involves the square root of sum of squares of differences of x-intercepts and y-intercepts.

The formula is given by:

[tex]d = \sqrt{(x_{2} -x_{1} )^{2}+(y_{2}- y_{1} )^{2} }[/tex]

Here,

[tex](x_{1},y_{1}) = (4,6)\\ (x_{2},y_{2}) = (7,-3)\\Putting\ the\ values\\d = \sqrt{(7-4)^{2}+(-3-6)^{2}}[/tex]

Hence, the following expression will give the distance between given points

[tex]d = \sqrt{(7-4)^{2}+(-3-6)^{2}}[/tex]

Solving it will give:

[tex]d = \sqrt{(3)^{2}+(-9)^{2}}\\= \sqrt{9+81}\\=\sqrt{90}[/tex]

Contains the points (-6, -12), (0, -12)
put into slope intercept form ASAP ​

Answers

Answer:

y=-12

Step-by-step explanation:

For the slope of line given two points I like to line up and subtract. Then put 2nd diff/1st diff.

Let's do that:

(-6  , -12 )

(0 ,  -12)

-----------

-6      0

2nd/1st=0/-6=0  slope should have been obvious as 0 since there is no rise in the points (you can see this from their y-coordinate)

Anyways the y-intercept is when it crosses the y-axis. The y-axis is crossed when the x-coordinate is 0. You have that given here which is -12.

So the equation is y=0x-12 or jusy y=-12

If you already knew that horizontal lines were of the form y=a number

then you could have just skip to y=-12

y=-12 just means all the ordered pairs on this line have the y-coordinate being -12 which is what we have in the set of points you gave

Which is a correct first step in solving the inequality -4(2x-1)>5-3x

Answers

The correct first step of solving the inequality problem -4(2x-1)>5-3x is that

Expand -4(2x-1): -8x+4

You apply the distributive laws
a=4, b=2x, c=1
= -4x time 2x-(-4) time 1

Simplify -4 time 2x+4 time 1
Multiply the numbers: 4 time2=8
= -8x+4

Multiply the numbers: 4time1=4
= -8x+4

Answer:

Apply distributive property that's the first step.

Step-by-step explanation:

The given inequality is

[tex]-4(2x-1)>5-3x[/tex]

The first step we need to do is to apply distributive property to relase the binomial inside the parenthesis

[tex]-8x+4>5-3x[/tex]

Then, we move all variables to the left side, and all constants to the right side

[tex]-8x+3x>5-4\\-5x>1[/tex]

Now, we divide the inequality by -5, which changes the sign orientation

[tex]\frac{-5x}{-5} <\frac{1}{-5}\\ x<-\frac{1}{5}[/tex]

Therefore, the solution is a set with all values less than -1/5. The graph attached shows this solution.

exact value of sin(11pi/12)

Answers

Final answer:

The exact value of sin(11π/12) is (√6 - √2)/4.

Explanation:

To find the exact value of sin(11π/12), we can use trigonometric identities to determine the value of an equivalent angle in the first quadrant. Since π/12 is the reference angle of 11π/12, which is in the second quadrant, we can find the sine of the equivalent angle in the first quadrant. The reference angle in the first quadrant is π/12. Therefore, the exact value of sin(11π/12) is the same as the exact value of the sine of π/12. Using a trigonometric identity, we find that sin(π/12) = (√6 - √2)/4.

Learn more about Trigonometric Identities here:

https://brainly.com/question/24377281

#SPJ12

What is the quotient of the polynomials shown below?

Answers

Answer:

Option A is correct.

Step-by-step explanation:

We need to find the quotient of the polynomials

[tex](6x^3+8x^2+16)\div(2x+4)[/tex]

The quotient is: 3x^2-2x+4

The remainder is: 0

The division is shown in the figure attached.

Option A is correct.

What is the mean of this data set

14, 12, 21, 26, 19, 15, 22, 17, 24, 18

Answers

The mean of this data set is 18.8

Answer:

The mean of this data set is  [tex]\mu = 18.8[/tex]

Step-by-step explanation:

By definition, the mean of a data set [tex]x_1, x_2, x_3, ..., x_n[/tex] is

[tex]\mu = \frac{\sum^n_i x_i}{n}[/tex]

Where n is the total number of data.

In this case we have 10 data

14, 12, 21, 26, 19, 15, 22, 17, 24, 18

So the mean is:

[tex]\mu = \frac{14 +12 +21 +26 +19 +15 +22+ 17 +24 +18}{10}[/tex]

[tex]\mu = 18.8[/tex]

What is 70% of 420

Answers

Hello There!

70% of 420 is 294

You want to divide 70% by 100 and you get a quotient of 0.7

Next, you want to multiply that by 420 because your trying to find 70% of it.

Finally, once you multiply you will get a product of 294.

Have A Great Day!

What is the slope of the line shown below? (-1,8) and (2,-4)

Answers

Answer:

[tex]m = -4[/tex]

Step-by-step explanation:

[tex]\frac{y2 - y1}{x2 - x1}[/tex]

[tex]\frac{-4 - 8}{2-(-1)}[/tex]

[tex]-4 - 8 = -12\\ 2-(-1)=3[/tex]

[tex]\frac{-12}{3} = -4[/tex]

[tex]m = -4[/tex]

Answer:

M=-4

Step-by-step explanation:

The formula for the slope is:

m=[tex]\frac{y^{2} -y^{1} }{x^{2} -x^{1} }[/tex]

You have two points the first one would be: (-1,8)

So [tex]x^{1}= -1  y^{1}= 8 [/tex]

The second point is: (2,4)

So [tex]x^{2}= 2  y^{2}= 4 [/tex]

Now you just have to put the values inside the formula:

m=[tex]\frac{-4-8)}{2-(-1)}[/tex]

m=[tex]\frac{-12}{3}[/tex]

m=-4

What is the intersection of a plane and a solid figure called?

Answers

Answer: Cross section

Step-by-step explanation: A cross section sounds just like what it is. It’s a plane that intersects a solid figure. A cross section can happen on any solid figure.

Find the solution of this system of equations.
Separate the x- and y-values with a comma.
X + 12y = 17
x - y = -9
Enter the correct answer.

Answers

Answer:

(-7, 2).

Step-by-step explanation:

x + 12y = 17

x - y = -9

Subtracting:

0 + 13y = 26

y = 2.

Substitute for y in the second equation:

x - 2 = -9

x = -7.

Answer:

{-7,2}

Step-by-step explanation:

Given

x+12y=17     Eqn 1

x-y=-9          Eqn 2

We will use the substitution method to solve the system of equations. So, from eqn 2:

[tex]x-y=-9\\x=y-9[/tex]

Putting the value of x in equation 1:

[tex](y-9)+12y=17\\y-9+12y=17\\y+12y-9=17\\13y=17+9\\13y=26\\\frac{13y}{13}=\frac{26}{13}\\ y=2[/tex]

Putting the value of y in eqn 2:

[tex]x-2=-9\\x=-9+2\\x=-7\\So,\\Solution set = \{-7,2\}[/tex]


Giving 20 points please get it right

Answers

Answer:

10

Step-by-step explanation:

Leave the 5 , change division to multiplication and turn the fraction upside down.

5 × [tex]\frac{2}{1}[/tex] = 5 × 2 = 10

If it takes 10 men 6 days to build a house how long would it take 4

Answers

Answer:

15 days

Step-by-step explanation:

10 men : 6 days

4 men : ? days

? = 15

Other Questions
What is the densest layer In triangle ABC, an altitude is drawn from vertex C to the line containing AB. The length of this altitude is h and h=AB. Which of the following is true?I. Triangle ABC could be a right triangle.II. Angle C cannot be a right angle.III. Angle C could be less than 45 degrees. According to a recent study, 9.2% of high school dropouts are 16- to 17-year-olds. In addition, 6.2% of high school dropouts are white 16- to 17-year-olds. What is the probability that a randomly selected dropout is white, given that he or she is 16 to 17 years old? PLZ HELP, 20 pts and brainliest awarded, plz ASAP!!!!!!see image below Which factor places this nation in the transitioningcategory? A mover in a moving truck is suing a rope to pull a 400-pound box up a rampthat has an incline of 25o. What is the force needed to hold the box in astationary position to prevent the box from sliding down the ramp? What problem might a historian have when trying to use this book as a source for a historical arguement Which of the following risk factors can have an immediate impact on a persons health ? In a bouquet of 24 roses, sixteen are red and the rest are pink. What is the ratio of pink to red roses? The process of getting information out of memory is called Which of the following would not be involved in performing synergism when making a fist? a. Extensor Carpi Radialis Longus b. Extensor Digitoriumc. Extensor Carpi Radialis Brevis d. Extensor Carpi Ulnaris Factor completely: 2x2 + 10x + 12 Which of the following is NOT prohibited by Georgia law?A. Crossing a dividing section, barrier, or unpaved strip, which separates two roadways B. Coasting with the gears or transmission of the vehicle in neutral when traveling on a downgrade C. Entering or leaving any controlled-access (interstate) roadway at authorized entrances Which of the following is true? Multiple Choice A regressive tax rate structure imposes an increasing marginal tax rate as the tax base increases. Regressive tax structures are the most common tax rate structure. An example of a regressive tax is an excise tax. In terms of effective tax rates, a sales tax can be viewed as a regressive tax. What is the most important commodity in a postindustrial society?ElectricityMoneyInformationComputers Find -x + 10 subtracted from 0.-* +100X-10 What was the name of the Puritan group that wanted to separate from the Church of England? A. Quakers B. Pilgrims C. Catholics D. Dissenters E. Jews Until 1987, in cases of extradition,A. all fugitives were protected from extradition by their political beliefsB. all fugitives were protected from extradition by their raceC. the federal government could not force a state governor to return a fugitiveD. the federal government had the power to force a state governor to return a fugitive please help asap urgent brainliest The perimeter of a rectangle is 90 feet. The length is 27 feet.What is the width of the rectangle? in feet An object whose mass is 100 lb falls freely under the influence of gravity from an initial elevation of 600 ft above the surface of Earth. The initial velocity is downward with a magnitude of 50 ft/s. The effect of air resistance is negligible. Determine the velocity, in ft/s, of the object just before it strikes Earth. Assume g = 31.5 ft/s